Euthanasia and other end-of-life decisions: a mortality follow-back study in Belgium - Bossuyt Nathalie; Bilsen Johan; Deschepper Reginald; Van den Block Lieve; Van Casteren Viviane; Deliens Luc (BMC, 2009)
Abstract Background This study compares prevalence and types of medical end-of-life decisions between the Dutch-speaking and French-speaking communities of Belgium. This is the first nationwide study that can make these comparisons and the first measurement after implementation of the euthanasia law (2002). Methods We performed a mortality follow-back study in 2005-2006. Data were collected via the nationwide Sentinel Network of General Practitioners, an epidemiological surveillance system representative of all Belgian GPs. Weekly, all GPs reported the medical end-of-life decisions among all non-sudden deaths of patients in their practice. We compared the northern Dutch-speaking (60%) and southern French-speaking communities (40%) controlling for population differences. Results We analysed 1690 non-sudden deaths. An end-of-life decision with possible life-shortening effect was made in 50% of patients in the Dutch-speaking community and 41% of patients in the French-speaking community (OR 1.4; 95%CI, 1.2 to 1.8). Continuous deep sedation until death occurred in 8% and 15% respectively (OR 0.5; 95%CI, 0.4 to 0.7). Community differences regarding the prevalence of euthanasia or physician-assisted suicide were not significant. Community differences were more present among home/care home than among hospital deaths: non-treatment decisions with explicit life-shortening intention were made more often in the Dutch-speaking than in the French-speaking community settings (OR 2.2; 95%CI, 1.2 to 3.9); while continuous deep sedation occurred less often in the Dutch-speaking community settings (OR 0.5; 95%CI, 0.3 to 0.9). Conclusion Even though legal and general healthcare systems are the same for the whole country, there are considerable variations between the communities in type and prevalence of certain end-of-life decisions, even after controlling for population differences.